PROJECT-BASED LEARNING PADA RANCANGAN PENGELOLAAN PERSEDIAAN DI TFME POLITEKNIK NEGERI BATAM - Riri Zelmiyanti; Seto Sulaksono Adi Wibowo; Adhitomo Wirawab; Aulia Fajrin (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
The purpose of this study is to provide a design for inventory management at the Teaching Factory Manufacture Electronics (TFME) Batam State Polytechnic with a Project-Based Learning (PBL) review. In addition, this study also applies inventory recording in the second basic financial accounting course (AKD2). This study uses qualitative methods with exploratory and descriptive research classifications. The method of collecting data in this research is by direct interviews with the informants. Researchers also made direct observations in the field and collected the necessary data from the main data sources. The results of this study indicate the importance of managing inventory in TFME, one way of managing inventory is by making an inventory card. The inventory card design that has been made is expected to be able to control inventory and the inventory card is designed to be very easy to use, for the use of an inventory card, consistency is needed from all parties involved